2017
DOI: 10.33549/physiolres.933672
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Surfactant and Bacterial Lipopolysaccharide: The Interaction and its Functional Consequences

Abstract: The respiratory system is constantly exposed to pathogens which enter the lungs by inhalation or via blood stream. Lipopolysaccharide (LPS), also named endotoxin, can reach the airspaces as the major component of the outer membrane of Gram-negative bacteria, and lead to local inflammation and systemic toxicity. LPS affects alveolar type II (ATII) cells and pulmonary surfactant and although surfactant molecule has the effective protective mechanisms, excessive amount of LPS interacts with surfactant film and le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 100 publications
0
23
0
1
Order By: Relevance
“…Even though the LPS-induced ALI model has been established for years and widely used in pre-clinical studies, the accurate mechanisms of LPS-induced ALI are not yet fully understood [7,36]. Researchers have found that the excessive accumulation of ROS and a burst of inflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Even though the LPS-induced ALI model has been established for years and widely used in pre-clinical studies, the accurate mechanisms of LPS-induced ALI are not yet fully understood [7,36]. Researchers have found that the excessive accumulation of ROS and a burst of inflammatory cytokines (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some researchers have demonstrated that all of apoptosis, necroptosis, autophagy, and inflammation were involved in LPS-induced ALI [2,7,42,43]. To further evaluate each contribution to LPS-induced ALI, the LPS-induced BEAS-2B cell injury model was established in vitro, and the cells were treated with Fer-1 (2 μM, ferroptosis inhibitor), bongkrekic acid (BA, 20 μM, apoptosis inhibitor), necrostatin-1 (Nec-1, 50 μM, The results indicated that all of the inhibitors showed a rescue effect except bafilomycin A1, and apocynin had the best effect in the LPS-induced injury model in vitro compared with other inhibitors ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ATI cells are large, flat cells which cover approximately 90% of the alveolar surface, and their main roles are gas exchange and maintenance of fluid balance. A major function of small cuboidal ATII cells is the production of pulmonary surfactant, which is fundamental for preventing of alveolar collapse by reducing surface tension at the end of expiration, and plays an important role in the local pulmonary defense mechanisms in which mainly surfactant proteins (SPs) are involved [1,2]. ATII cells are also the main source of endogenous antimicrobial peptides; among them is cathelicidin hCAP18/LL-37 [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…0 control, FG fatty gauze, Alv at 0.01 and 0.5 mg/mL. phospholipids and the hydrophobic surfactant proteins SP-B and SP-C which ease the absorption and spreading of the surfactant film, phosphatidylglycerol (PG) 29,30 , DPPC 18 , SP-B 31 and SP-C 32 have anti-inflammatory and antibacterial 15 properties 8,14 . Interestingly, surfactant proteins are also secreted by amniotic 33 , skin 34 and mucosal cells 35 .…”
Section: Discussionmentioning
confidence: 99%